Student-Teachers’ Teaching Techniques: Actors in Pupils’ Extrinsic Motivation as They Speak - Báez Dueñas Leidy Tatiana; Chacón Vargas Leidy Marcela (Profile: Issues in Teachers' Professional Development)
<span style="font-size: 10.0pt; font-family: ";Verdana";,";sans-serif";; mso-fareast-font-family: ";Times New Roman";; mso-bidi-font-family: ";Times New Roman";; mso-ansi-language: EN-US; mso-fareast-language: ES-CO; mso-bidi-language: AR-SA;" lang="EN-US">This article describes a research project we carried out in order to study the role of student-teachers’ teaching techniques as regards their pupils’ extrinsic motivation as they partake in communicative speaking activities at a public school in Tunja, Colombia. Data were gathered by means of field notes, focus groups and student-teachers’ documents. Findings revealed that student-teachers assume different roles regarding their teaching techniques depending on the stage of the class (presentation, practice, and production). The techniques, at the same time, constitute the nature of these roles. Explorers, keepers, and producers were the main roles that participants assumed when they involved their students in communicative speaking activities. <span style="font-size: 10.0pt; font-family: ";Verdana";,";sans-serif";; mso-fareast-font-family: ";Times New Roman";; mso-bidi-font-family: ";Times New Roman";; mso-ansi-language: EN-US; mso-fareast-language: ES-CO; mso-bidi-language: AR-SA;" lang="EN-US">Este artículo describe un proyecto de investigación llevado a cabo para estudiar la función que tienen las técnicas de enseñanza empleadas por los docentes practicantes en la motivación extrínseca cuando sus estudiantes participan en actividades orales comunicativas, en un colegio público de Tunja (Colombia). Los datos se recolectaron por medio de notas de campo, grupos focales y los planes de clase de los futuros docentes. Los resultados revelaron que las técnicas de enseñanza empleadas por los practicantes tienen diferentes funciones dependiendo de la etapa de la clase (presentación, práctica o producción) en que se usen. Los principales papeles que los participantes adoptaron al involucrar a sus estudiantes en actividades orales comunicativas fueron: exploradores, cuidadores y productores.